A comparative assessment of multi-objective optimisation methodologies for aero-engine nacelles - Swarthout, Avery E.; MacManus, David G.; Tejero, Fernando; Matesanz García, Jesús; Boscagli, Luca; Sheaf, Christopher T. (International Council of the Aeronautical Sciences (ICAS), 2022)
There are significant environmental and economic drivers for the development of more fuel-efficient commercial aircraft engines. The propulsive efficiency benefits of ultra-high bypass ratio turbofans may be counteracted by the drag and weight penalty associated with larger nacelles. A more compact nacelle design may therefore be necessary to reduce these penalties. However, increasing compactness also increases the sensitivity of the nacelle to boundary layer separation under off-design windmilling conditions. This paper investigates methods for incorporating windmilling considerations alongside design point requirements within a multi-objective, multi-point optimisation. Windmilling under aircraft diversion and at the end-of-runway (EoR) condition are considered. The windmilling conditions are assessed through a combination of regression and classification type criteria. The transonic aerodynamics of the nacelle at the design point are notably different from the transonic characteristics at the diversion windmilling conditions. Meanwhile, the aerodynamics, and separation mechanisms, at the end-of-runway condition are dominated by subsonic diffusion. Overall, a combination of regression and classification mechanisms are found to be most suitable for the nacelle optimization as it delivers a design population which is favorably balanced between robustness against boundary layer separation as well as delivering nacelle drag benefits.
Keywords: nacelle; optimisation; CFD; off-design; separation